Feeding Behavior and Food Preferences of Bornean Orang utan (Pongo pygmaeus) at Gembira Loka Zoo Yogyakarta - Jati, Fajar Sanintan; Riawan, I Made Oka; Syah, Moh Jafron (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Feeding management is crucial in the care of orangutans in captivity, particularly the understanding of individual feeding preferences as a key factor in animal welfare. This study aims to review feeding management, identify preferences, and analyze the feeding behavior of Bornean orangutans (Pongo pygmaeus) at Gembira Loka Zoo, Yogyakarta. Observations were conducted on four accommodation individuals and two display individuals from May to July 2025, focusing on feeding position, technique, timing, and activity. The method used was descriptive observational with scan sampling from 08:00 to 15:00 local time, along with recording of feed types, weights, and leftovers. Preferences were analyzed using Jacobs’ Index (Di), categorized as highly preferred, preferred, less preferred, and not preferred, along with palatability assessment. Results showed that the main diet consisted of vegetables (64.90%), fruits (18.47%), and tubers (15.32%), with melon, tubers, and corn being the most preferred foods, while pumpkin and bok choy were less favored. Feeding behavior varied according to age, sex, social status, and activity level, dominated by sitting positions and techniques that demonstrated fine motor skills as well as adaptation to artificial environments. These findings are particularly beneficial for feeding management at Gembira Loka Zoo to minimize leftovers based on individual preferences, while also serving as a reference for improving animal welfare and the effectiveness of other ex situ conservation efforts.